MEDIA PEMBELAJARAN MONITORING INFUS BERBASIS INTERNET OF THING PADA MATA KULIAH APLIKASI MIKROKONTROLER - Manuhara, Agus Restu; Agus Adiarta; I Gede Made Surya Bumi Pracasitaram (Jurnal Pendidikan Teknik Elektro Undiksha, 2023)
This study aims to create an Internet Of Thing Based Infusion Monitoring Learning Media in Microcontroller Application Courses. This research is included in the type of R&D research (reasearch and development). This study uses percentage statistical analysis techniques to process data from content experts, media experts, and trials on students. This study used a questionnaire as an instrument for data collection for content experts, media experts, and students. The results of the research results of the content expert validation test obtained 96.1% with very decent qualifications, the media expert validation test obtained 98.5% with very decent qualifications, the results of the small group test of 5 student respondents got the lowest score of 43 with very good qualifications, and a percentage of 100% with very high qualification results, and the large group trial of 15 respondents got the lowest score of 42 with very good qualifications, and got a percentage of 100% with very high qualification results. Based on the results of the research, the Internet Of Thing Based Infusion Monitoring Learning Media is suitable for use in the learning process in Microcontroller courses in the Undiksha Electrical Engineering Education Study Program.